Growth Response in Small for Gestational Age in Comparison with Growth Hormone Deficient Children within the First Year of Growth Hormone Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Growth hormone is used to treat short stature and growth failure associated with growth disorders. Growth parameters at birth and growth hormone status variably modulate response to growth hormone therapy.Aim of the study: To compare growth response between short small for gestational age and growth hormone deficient children during the first year of growth hormone treatment and to see the differences between them at presentation regarding age and sex.Patients and methods: Randomized controlled trials were done at the Endocrine and Diabetic Center in the Central Teaching Hospital of Pediatric in Baghdad City within the period started from Nov. 1, 2021, to the end of Nov. 2022. The study population was 100 short prepubertal children aged between 3–13 years, 50 patients diagnosed with growth hormone deficiency (GHD) and 50 with small for gestational age (SGA), and both were arranged for growth hormone (GH) treatment; GHD group was classified according to growth hormone level in the provocation test into severe GHD (max GH 0.3), even in the SGA group but with a high dose of growth hormone. Also, as a comparison in HV between the two groups (GHD vs. SGA), the greatest response was in the GHD group with a significant P-value (p=0.002).Conclusion: Younger age at diagnosis and treatment with growth hormone are associated with better response in ΔHt SDS and growth velocity for both small for gestational age and growth hormone deficient patients. High dose of growth hormone (>0.045µg/kg/day) is associated with better response in ΔHt SDS and growth velocity in the first-year treatment in SGA patients. In a comparison in response after one year of treatment with growth hormone between GHD and SGA children, the response to GH treatment was significantly better in the GHD group than in the SGA group in ΔHt SDS and growth velocity; moreover, both of them had a good response to GH after first-year treatment (ΔHt SDS >0.3).